DEMOGRAPHIC SEGMENTATION IN THE DISTRIBUTION OF HOME OWNERSHIP FINANCING (KPR) AT BANK SYARIAH INDONESIA KC PALANGKARAYA - Rahmad Kurniawan; Itsla Yunisva Aviva; Oktafiana Putri Kinanti (Fakultas Ekonomi dan Bisnis Islam, 2023)
Introduction/ Purpose: Segmentation is very important in the world of banking. Segmentation plays an important role and is the basis for banking players to position their products so they are different from their competitors. This research seeks to examine the application of demographic segmentation in the distribution of housing finance (KPR) at Bank Syariah Indonesia KC Palangkaraya Diponegoro. And the effectiveness of applying demographic segmentation in the distribution of home ownership financing (KPR) at Bank Syariah Indonesia KC Palangkaraya Diponegoro. Research Methods: The method used in this study is a qualitative method with descriptive qualitative method and the type is intrinsic case study, the data collection method is by observation, interviews and documentation. This research was conducted at Bank Syariah Indonesia KC Palangkaraya Diponegoro with research subjects namely Consumer Business Relationship Manager (CBRM) and Consumer Business Staff (CBS), while the object was the application of demographic segmentation in financing home ownership at Bank Syariah Indonesia KC Palangkaraya Diponegoro. Results: The results showed The application of demographic segmentation at Bank Syariah Indonesia KC Palangkaraya Diponegoro can easily classify customers by occupation, based on income, age and domicile, which are the main requirements assessed by Bank Syariah Indonesia in disbursing home ownership financing to determine the character of a customer. The effectiveness of applying demographic segmentation at Bank Syariah Indonesia is considered not effective in terms of work, it is proven that Bank Syariah Indonesia focuses on permanent employee customers..